Clinicopathological correlations and cellular dynamics in a murine model of oral carcinogenesis - Bueno, Cheyenne Coscia; Klein, Isadora Peres; Andrades, Michael Everton; Meurer, Luise; Castilho, Rogério Moraes de; Klein, Caroline Peres; Wagner, Vivian Petersen; Martins, Manoela Domingues; Carrard, Vinicius Coelho (Journal of Oral Diagnosis, 2025)
Objective: To investigate clinicopathological correlations, cell proliferation, and immortalization during induced oral carcinogenesis. Methods: Forty-three Wistar rats were divided into a control group (n=10) or a 4-Nitroquinoline 1-oxide (4NQO) group (n=33). Control animals were euthanized after 20 weeks, and 4NQO-treated animals after 4 (n=10), 12 (n=10), or 20 weeks (n=13). Oral lesions were classified macroscopically and histologically, with Ki-67 and BMI-1 immunolabeling used to assess cell proliferation and immortalization. Results: Histological alterations, including hyperplasia/hyperkeratosis (n=4) and severe dysplasia (n=2), were observed in clinically normal mucosa. Leukoplakic lesions exhibited varying severity, ranging from hyperplasia/hyperkeratosis (n=3) to squamous cell carcinoma (SCC, n=2). Most SCCs appeared as ulcers (n=3) or nodules (n=4). Ki-67 expression increased progressively with histopathological changes, while BMI-1 levels rose significantly in later stages. A positive correlation was found between Ki-67 and BMI-1 (R=0.33, p=0.03). Conclusion: Cellular alterations often precede visible clinical lesions. Clinical appearances, particularly of leukoplakic lesions, frequently did not align with histopathological findings. Proliferation and immortalization were interconnected but occurred at distinct stages of carcinogenesis.